2019
DOI: 10.1016/j.eneco.2019.104507
|View full text |Cite
|
Sign up to set email alerts
|

Income inequality and carbon consumption: Evidence from Environmental Engel curves

Abstract: This paper analyses the relationship between the distribution of income and the carbon dioxide content of household consumption. Household carbon is estimated by linking expenditure data to productive sectors and their carbon intensity derived through input-output analysis. Environmental Engel curves (EECs) are estimated, which describe the relationship between household income and CO 2 in the United States between 1996 and 2009. A second-degree polynomial specification in income is found to approximate well t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
66
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(70 citation statements)
references
References 53 publications
2
66
1
1
Order By: Relevance
“…Fig 1 shows the scatter plot of air pollution and income inequality in 156 countries or regions (hereinafter collectively referred to as countries). As shown in Fig 1, there is a clear positive correlation between air pollution and income inequality [20,23]. Although this differs from most previous research conclusions [16,22,24], it provides evidence for the impact of air pollution on income inequality.…”
Section: Introductioncontrasting
confidence: 67%
“…Fig 1 shows the scatter plot of air pollution and income inequality in 156 countries or regions (hereinafter collectively referred to as countries). As shown in Fig 1, there is a clear positive correlation between air pollution and income inequality [20,23]. Although this differs from most previous research conclusions [16,22,24], it provides evidence for the impact of air pollution on income inequality.…”
Section: Introductioncontrasting
confidence: 67%
“…Golley and Meng (2012), Baek and Gweisah (2013), Jorgenson (2015), Kasuga and Takaya (2017), , and Uzar and Eyuboglu (2019) came to the conclusion that higher CO 2 emissions were positively associated with increasing income inequality [34][35][36][37][38][39]. In contrast, Heerink et al (2001), Coondoo and Dinda (2008), Baloch et al (2017), Hübler (2017), and Sager (2019) held that inequality affected carbon emissions in the opposite direction [28,[40][41][42][43]. Using an unbalanced panel data set from 158 countries, Grunewald et al (2017) found that the impact of income inequality on carbon emissions varied with economic development levels [44].…”
Section: Introductionmentioning
confidence: 97%
“…Based on these discussions, it is clear that most of the existing literature investigates the effect of income inequality on carbon emissions focused on the national level, state level, or city level; however, few studies concern about the micro behavior body: the households. Based on the United States Consumer Expenditure Survey (CEX) from 1996 to 2009, Sager (2019) estimated the Environmental Engel curves (EECs) and examined the effects of different factors on the evolution of carbon emissions over time [43]. He found that income, age structure, education, family size, race, and region were relevant, and among these factors, income played a major role.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we choose to quantify inequality via Lorenz curves. The Lorenz curve has considerable intuitive appeal and is widely used to analyze the evolution of inequality in energy consumption 5/26 (Jacobson et al, 2005;Lawrence et al, 2013) and CO2 emissions (Groot, 2010;Sager, 2019;Zimm and Nakicenovic, 2019). This is due to its graphical depiction of inequality as the divergence of the Lorenz curve from the perfect equality diagonal.…”
Section: Inequality In the Cap And Floor Scenarios Of Carbon Footprintsmentioning
confidence: 99%